2014
DOI: 10.1007/s00330-014-3542-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing liver function in patients with HBV-related HCC: a comparison of T1 mapping on Gd-EOB-DTPA-enhanced MR imaging with DWI

Abstract: • T 1 mapping on Gd-EOB-DTPA MRI was accurate for assessing liver function. • HBP T 1 relaxation time measurement was as accurate as ∆% T 1 • T 1 mapping on Gd-EOB-DTPA MRI was more accurate than DWI-ADC measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 31 publications
2
32
2
Order By: Relevance
“…Two recent studies by Kamimura et al [21] and Ding et al [20] have assessed the utility of T1 relaxometry before and after gadoxetic acid administration for the assessment of liver cirrhosis and liver function using a 3D-DFA technique at a 3 T (n = 99 patients) and 1.5 T (n = 100 patients) system respectively showing that this technique has potential to serve as an MRI-based liver function test. Compared to these studies, our study provides in-vitro validation of T1 relaxation values and information on intra-patient variability of T1 values in the largest published series of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies by Kamimura et al [21] and Ding et al [20] have assessed the utility of T1 relaxometry before and after gadoxetic acid administration for the assessment of liver cirrhosis and liver function using a 3D-DFA technique at a 3 T (n = 99 patients) and 1.5 T (n = 100 patients) system respectively showing that this technique has potential to serve as an MRI-based liver function test. Compared to these studies, our study provides in-vitro validation of T1 relaxation values and information on intra-patient variability of T1 values in the largest published series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have examined the ability of gadoxetic acid T1 relaxometry for diagnosing liver fibrosis and for prediction of liver Magnetic Resonance Imaging 33 (2015) 1075-1082 function [18][19][20][21] showing good results for assessment of severity of liver cirrhosis with significant differences in T1 relaxation times of the liver after gadoxetic acid administration between patients with normal liver function and patients with Child-Pugh A, B, and C cirrhosis. These data showed that this technique might provide suitable parameters for detecting and characterizing severity of cirrhosis.…”
Section: Introductionmentioning
confidence: 98%
“…All MRIs were performed with a 1.5T MR scanner (Magnetom Aera, Siemens Healthcare, Erlangen, Germany) using a phased‐array body coil. Transverse T 1 mapping consisted of a 3D gradient‐echo, volumetric interpolated breath‐hold examination (VIBE) with a dual flip‐angle (FA) of 2° and 12°, as described previously . The parameters were as follows: echo time (TE) 1.93 msec, repetition time (TR) 4.38 msec, field of view (FOV) (380–400) mm × (300–324) mm, matrix = 216 × 288, slab thickness 20 cm interpolating into a slice thickness of 5 mm, generalized autocalibrating partially parallel acquisition (GRAPPA) with an acceleration factor of 2.…”
Section: Methodsmentioning
confidence: 99%
“…A predictive nomogram and a CNN including imaging data with high performance for toxicity prediction after liver SBRT are already available [57,100]. Generally, toxicity analysis in healthy liver tissue should be improved even more, since MRI enables accurate liver function analysis and radiomics analysis allows for accurate staging of liver fibrosis and may prevent and, vice versa, predict RILD [101][102][103][104].…”
Section: Target Volume Definition: Automatic Segmentation Of Target Vmentioning
confidence: 99%